THE INFLUENCE OF INFLATION, BI RATE AND NON PERFORMING FINANCE ON PROFITABILITY 2014-2018 PERIOD - Inventa, Tria; Sidik, Solihin (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
The purpose of this study was to determine, explain and analyze the partial and simultaneous influence of Inflation, Bi Rate and Non Performing Finance on Profitablity. The independent variables used in this study are Inflas, BI Rate and Non Perfoming Finance while the dependent variable in this study is profitability. The population in this study is the 2014-2018 Sharia General Banking Company. The sampling technique used is purposive sampling. The method used in this research is descriptive and verification methods. Based on the results of the analysis of research data, several conclusions are obtained as follows: (1) Inflation partially has a negative effect and significant Profitability at Sharia Commercial Banks in the study period, BI Rate partially has no effect on Profitability at Sharia Commercial Banks in the study period and Non Performing Finance has a negative effect and significant towards profitability at Islamic commercial banks in the research period. (2) Inflation, BI Rate and Non Performing Finance have a positive and significant effect on profitability (ROA) at Islamic Commercial Banks in the study period.